The Effect of Using Mind Mapping Strategy on the Students’ Skill in Writing Recount Text - Sembiring, Friscilla (Pascasarjana Universitas HKBP Nommensen, 2020)
This study is intended to find out the effect of using Mind Mapping Strategy on The Students’ Skill in Writing Recount Text. It is an experimental study. There are eleven classes of them. Since the study needs two groups (Experimental and control group), two classes are taken by using random sampling technique. The two classes have 60 students. The experimental group is taught by applying mind mapping strategy and the control group is taught by applying Conventional Method. The instrument for collecting the data is writing recount text about holiday. It is consisted of 100 words. After the data has been scored, the data is analyzed by using t-test formula. The analysis shows that t-test is 3.75 while t-table is 2.000.It means that t-test is higher than t-table with the degree of freedom 58, and the level of significance 0.05. The result shows that the hypothesis of this study is accepted. In other words, Mind Mapping Strategy significantly affects the students’ writing skill in recount text.